The State-Trait Anxiety Inventory - Spielberger, Charles D.; Gonzalez-Reigosa, Fernando; Martinez-Urrutia, Angel; Natalicio, Luiz F.S.; Natalicio, Diana S. (Revista Interamericana de Psicología/Interamerican Journal of Psychology, 2017)
The goal of this study was to describe the construction of scales for measuring- state (A-State) and trait (A-Trait) anxiety that would be suitable for use in interamerican, cross-cultural research. The State-Trait Anxiety Inventory (Spielberger, et al., 1970) was translated into Spanish with the assistance of psychologists from 10 different Latin American countries. To evaluate the reliability and equivalence of the Spanish and English forms of the STAI, these scales were given in counterbalanced order to bilingual 5s in Texas and Puerto Rico. In both samples, high item- remainder correlations and alpha coefficients ranging from .82 to .95 established the internal consistency of the Spanish A-State and A-Trait scales. Evidence of the equivalence of these scales was provided by correlations between the Spanish and English forms that ranged from .83 to .94. High test-retest reliability was also found for the Spanish A-Trait scale but not for the A-State scale. As expected, the A-State scale was influenced by transitory situational stress, whereas the A-Trait scale was stable over time. It was concluded that the Spanish STAI provides internally consistent and reliable scales for measuring state and trait anxiety which are essentially equivalent to the English STAI A-State and A-Trait scales.